The effect of salary, work-life balance, working environment, and supervisory support on job satisfaction among employees in private organizations - Rusdan, Hasan (2025)
Job satisfaction plays a crucial role in influencing employee performance and the overall success of an organization. Satisfied employees are generally more productive, engaged, and committed to their roles. In contrast, dissatisfaction can lead to reduced morale, increased absenteeism, and high turnover rates. Recognizing these implications, this study aims to examine the effects of four key workplace factors: salary, work-life balance, working conditions, and supervisory support on job satisfaction among employees in selected private organizations located in Kuala Lumpur and Shah Alam, Malaysia. A quantitative research design was adopted for this study. Data were collected through a structured online questionnaire administered to 250 employees from diverse industries and job levels. A total of 150 usable responses were obtained and analyzed using the Statistical Package for the Social Sciences (SPSS) version 24. Pearson correlation analysis was conducted to identify associations between the variables, while multiple regression was employed to determine the strength of each workplace factor on job satisfaction. The findings reveal that salary, working conditions, and supervisory support have a significant and positive relationship with job satisfaction, indicating that enhancements in these areas are likely to boost employees’ satisfaction levels. Conversely, work-life balance did not demonstrate a statistically significant effect, suggesting it is not a primary predictor of job satisfaction in the sampled context. These results imply that other workplace factors may play a more prominent role. The study offers valuable insights for human resource practitioners and organizational management in designing targeted strategies to improve employee job satisfaction, particularly within the private sector landscape in Malaysia.